Peran Video Marketing sebagai Variabel Intervening dalam Menentukan Keputusan Berbelanja di Aplikasi Tiktok Shop pada Konsumen Indonesia - Firdaus; Mulyanto, Kukuh; Rusmiyatun; Sitti Nurrahmah, Wa Ode; Jatmiko, M. Roby (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2023)
The development of the world of information technology is directly proportional to the behavior of consumers in Indonesia in meeting their daily needs. It can be seen from how consumptive the Indonesian people are to buy products online, one application that is currently favored by the public for online shopping is the Tiktok Shop application. This research was conducted to predict the relationship between variables that are used by the community as a determinant in making decisions to shop on the Tiktok Shop application, besides that it wanted to prove the role of video marketing in the Tiktok Shop application. Collecting data in this study used a questionnaire with a purposive sampling technique with a total of 100 respondents using the tiktok shop application. The results of this study prove that Indonesian consumers in making product purchase decisions because they often see stories from social media and search engine optimization can directly influence consumers to shop on the Tiktok Shop application. In addition, video marketing broadcast by content creators can strengthen or bridge consumers to buy products in the Tiktok Shop application.